Inschriften im ägyptischen Museum Leipzig - Georg Steindorff - der Universität Leipzig. (Kleine Schriften des Agyptischen Museums der Universitat Leipzig ;, 2016)
This book covers a large part of the period of time in which hieroglyphs and derived scripts including the alphabetically written coptic were used. From hieroglyphic inscriptions on steles and sarcophagi, wishful phrases on amulets through schoolbooks, employment contracts and debts in hieratic script, to an insight into the Mesopotamian cuneiform culture, this volume offers an exciting insight into the different areas of ancient Egyptian life